Perception of Water-Based Masking Sounds—Long-Term Experiment in an Open-Plan Office - Hongisto, Valtteri; Varjo, Johanna; Oliva, David; Haapakangas, Annu; Benway, Evan (Frontiers in Psychology, 2017)
A certain level of masking sound is necessary to control the disturbance caused by speech sounds in open-plan offices. The sound is usually provided with evenly distributed loudspeakers. Pseudo-random noise is often used as a source of artificial sound masking (PRMS). A recent laboratory experiment suggested that water-based masking sound (WBMS) could be more favorable than PRMS. The purpose of our study was to determine how the employees perceived different WBMSs compared to PRMS. The experiment was conducted in an open-plan office of 77 employees who had been accustomed to work under PRMS (44 dB LAeq). The experiment consisted of five masking conditions: the original PRMS, four different WBMSs and return to the original PRMS. The exposure time of each condition was 3 weeks. The noise level was nearly equal between the conditions (43 - 45 dB LAeq) but the spectra and the nature of the sounds were very different. A questionnaire was completed at the end of each condition. Acoustic satisfaction was worse during the WBMSs than during the PRMS. The disturbance caused by three out of four WBMSs was larger than that of PRMS. Several attributes describing the sound quality itself were in favor of PRMS. Colleagues’ speech sounds disturbed more during WBMSs. None of the WBMSs produced better subjective ratings than PRMS. Although the first WBMS was equal with the PRMS for several variables, the overall results cannot be seen to support the use of WBMSs in office workplaces. Because the experiment suffered from some methodological weaknesses, conclusions about the adequacy of WBMSs cannot yet be drawn.